Perbedaan Hukuman Bagi Pelaku Pembunuhan dalam Islam dan Pidana - Bagus Hadi Mustofa (IJoIS: Indonesian Journal of Islamic Studies, 2020)
Abstract. A lost heart often causes people to fall into behavior that deviates from the ethics, norms, religion, and laws that exist in human life. Murder is one of the actions that deviate from ethics in everyday life, killing is also strictly prohibited by religion. In Indonesia, the perpetrator of murder is punished according to the type of murder committed. In Indonesia premeditated murder carries a very serious penalty than unplanned murder. Every person who believes must be completely able to avoid various forms of murder and crime.